ANALISA KEBERADAAN SISA KLOR BEBAS PADA JARINGAN DISTRIBUSI PDAM KABUPATEN BANTUL DENGAN EPANET 2.0 - Agfian Ijlal Ramadhan; Naniek Ratni J.A.R (EnviroUS, 2021)
ABSTRACT The quality of clean water is a standard for drinking water companies when water is distributed from a Clean Water Treatment Installation (CWTI). Tto remove all particles from the raw there is important processing steps to obtain clean water such as pathogenic bacteria so that it is suitable for consumption. To remove of these pathogenic bacteria, using disinfection. The disinfectant that is often used is chlorine. The purpose is to analyze the presence of free chlorine residual in the distribution network of PDAM Bantul Regency with EPANET 2.0. This study is a quantitative study using correlation and regression analysis, while descriptive analysis is explained through tables and graphs. Sampling using purposive sampling as many as 80 samples. According to Permenkes RI 736 / MENKES / PER / VI / 2010, the average residual chlorine in the distribution pipe for the morning and afternoon. Also the conditions for an average temperature of ± 3 ° C and a pH range of 6.5 - 8.5 have been met. There is a relationship about the decreasing concentration of residual chlorine, the higher the pH value, but there is no correlation between temperature and residual chlorine.